Structural changes of the multifidus in animal models of intervertebral disk degeneration: a systematic review - Wang, Yaobin; Zhao, Xinghua; Zhang, Xiangyu; Yang, Yuhua; Zhang, Weikang; Liu, Shaocheng; Liu, Zhenlei; Zhang, Lei; Wang, Kai; Wu, Hao (Frontiers in Surgery, 2024)
Study designLow back pain (LBP) is a widespread clinical symptom affecting nearly all age groups and is a leading cause of disability worldwide. Degenerative changes in the spine and paraspinal tissues primarily contribute to the etiology of LBP.ObjectivesWe conducted this systematic review of animal models of paraspinal muscle (PSM) degeneration secondary to degenerative intervertebral disc (IVD), providing a comprehensive evaluation of PSM structural changes observed in these models at both macroscopic and microscopic levels.MethodsPubMed, EMBASE, Web of Science, Cochrane Library, and MEDLINE Ovid databases were searched through November 2023. Literature was sequentially screened based on titles, abstracts, inclusion of animal models and full texts. A manual search of reference lists from all eligible studies was also performed to identify any eligible article. Two independent reviewers screened the articles according to inclusion and exclusion criteria. The risk of bias was assessed using the Systematic Review Centre for Laboratory Animal Experimentation's Risk of Bias tool.ResultsA total of nine studies were included in the final analysis after a comprehensive screening process. The included studies were assessed for various aspects of the multifidus muscle. Given the limited number of studies and the substantial heterogeneity among them, a quantitative meta-analysis was deemed inappropriate.ConclusionsThis systematic review shows a comprehensive analysis of structural changes in the multifidus muscle in animal models of IVD degeneration and offers crucial insights for developing improved rodent models of IVD degeneration and assessing a battery of approaches for multifidus degeneration.